"Carbon‐Centered Radical Addition to O=C of Amides or Esters as a Route to C‐O Bond Formations" Remains Elusive. Issue 32 (24th May 2019) - Metzger, Jürgen O.
Abstract : "Carbon‐Centered Radical Addition to O=C of Amides or Esters as a Route to C‐O Bond Formations" was recently claimed by Liu et al. and published in this journal. However, is there really experimental or computational evidence for this reaction? This question is discussed in more detail in this Correspondence article